Searching for phylogenetic patterns of Symbiodiniaceae community structure among Indo-Pacific Merulinidae corals - Sébastien Leveque (PeerJ, 2019)
Over half of all extant stony corals (Cnidaria: Anthozoa: Scleractinia) harbour endosymbiotic dinoflagellates of the family Symbiodiniaceae, forming the foundational species of modern shallow reefs. However, whether these associations are conserved on the coral phylogeny remains unknown. Here we aim to characterise Symbiodiniaceae communities in eight closely-related species in the genera Merulina, Goniastrea and Scapophyllia, and determine if the variation in endosymbiont community structure can be explained by the phylogenetic relatedness among hosts. We perform DNA metabarcoding of the nuclear internal transcribed spacer 2 using Symbiodiniaceae-specific primers on 30 coral colonies to recover three major endosymbiont clades represented by 23 distinct types. In agreement with previous studies on Southeast Asian corals, we find an abundance of Cladocopium and Durusdinium, but also detect Symbiodinium types in three of the eight coral host species. Interestingly, differences in endosymbiont community structure are dominated by host variation at the intraspecific level, rather than interspecific, intergeneric or among-clade levels, indicating a lack of phylogenetic constraint in the coral-endosymbiont association among host species. Furthermore, the limited geographic sampling of four localities spanning the Western and Central Indo-Pacific preliminarily hints at large-scale spatial structuring of Symbiodiniaceae communities. More extensive collections of corals from various regions and environments will help us better understand the specificity of the coral-endosymbiont relationship.